2009
DOI: 10.1007/s00259-009-1225-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclisome: a novel concept for radionuclide therapy using targeting liposomes

Abstract: The results thus provide encouraging evidence that our two-step targeting strategy for tumour cell DNA has the potential to become an effective therapy against metastasizing cancer cells in the bloodstream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…By use of cellular assays that permitted quantification of the receptor-mediated uptake of the particles, we could confirm that the Nuclisome-particles are indeed taken up by the cultured cells through interaction with EGFR and HER2, respectively [32,33]. Importantly, the above studies showed that when receptors were blocked with an excess amount of free ligand, or liposomes were administered without targeting agent, the tumor-cell uptake was clearly suppressed.…”
Section: Target Specificitymentioning
confidence: 74%
See 4 more Smart Citations
“…By use of cellular assays that permitted quantification of the receptor-mediated uptake of the particles, we could confirm that the Nuclisome-particles are indeed taken up by the cultured cells through interaction with EGFR and HER2, respectively [32,33]. Importantly, the above studies showed that when receptors were blocked with an excess amount of free ligand, or liposomes were administered without targeting agent, the tumor-cell uptake was clearly suppressed.…”
Section: Target Specificitymentioning
confidence: 74%
“…The EGF-PEG-lipid and F5-PEG-lipid conjugates have subsequently been incorporated into liposomes composed of DSPC, cholesterol, and DSPE-PEG2000 (see e.g. [32,33]). Finally, the liposomes have been loaded with iodinated Comp1 using the pH-gradient-driven loading protocol which was first suggested by Mayer et al [34].…”
Section: Target Specificitymentioning
confidence: 99%
See 3 more Smart Citations